Sleep Hygiene for Healthy Sleep- General and Homoeopathic Measures (Homoeopathy for All, 2024)
Sleep is an opportunity for the brain  and body to rest and be restored. In  addition, many functions important  to good health take place during  sleep at night. In India, at least 10%  of the people can’t sleep without the  sleeping pills. Some sleep disorders  are serious enough to interfere  with normal physical, mental and  emotional functioning. This article  review about causes, risk factors,  different type, clinical presentation  general management including  some home remedies management  and homoeopathic way of treatment  of sleep disorder and healthy sleep.  Homoeopathy treats the person as a  whole. It means that homoeopathic  treatment focuses on the patient as  a person, as well as his pathological  condition.
Keywords: presentation; Homoeopathy; clinical